1979
DOI: 10.1111/j.1399-0004.1979.tb01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive myoclonus epilepsy: genetic and nosological aspects with special reference to 107 Finnish patients

Abstract: In 107 Finnish patients with progressive myoclonus epilepsy (PME), belonging to 74 families, autosomal recessive inheritance was evident. The sex ratio was 48:51, the corrected proportion of affected sibs being 0.260. Of 68 marriages 15, or 22 %, were consanguineous; several of the parents were related and the geographical distribution was of the uneven type typical of young, isolated populations in Finland. The incidence in Finland was estimated to exceed 1:20,000. The clinical picture in the Finnish PME pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(57 citation statements)
references
References 37 publications
5
52
0
Order By: Relevance
“…Moreover, patients carrying such a mutation are more likely to have a severer form of the disease resulting in severer myoclonus and treatment-resistant epileptic seizures. It has previously been reported that in EPM1, the epileptic seizures have a positive response to antiepileptic drug treatment [16] and tend to decrease in frequency or cease completely within 10-15 years from the onset of the disease [2,17] . We found that 3 of the compound heterozygous patients, with a disease duration of over 10 years, were still suffering from tonicclonic seizures despite extensive antiepileptic drug treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, patients carrying such a mutation are more likely to have a severer form of the disease resulting in severer myoclonus and treatment-resistant epileptic seizures. It has previously been reported that in EPM1, the epileptic seizures have a positive response to antiepileptic drug treatment [16] and tend to decrease in frequency or cease completely within 10-15 years from the onset of the disease [2,17] . We found that 3 of the compound heterozygous patients, with a disease duration of over 10 years, were still suffering from tonicclonic seizures despite extensive antiepileptic drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…128, FOV 256 ! 256 mm 2 , 73 axial slices with slice thickness of 2 mm) with diffusion gradients (b-values 0 and 1,000 s/mm 2 ) applied in 30 directions.…”
Section: Mr Imaging and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Its prevalence is estimated in 1-20,000 live births and mutations in the gene encoding cystatin B (CSTB), a cysteine protease inhibitor, are responsible for the EPM1 defects [1,3,[6][7][8].…”
Section: Unverricht-lundborg Diseasementioning
confidence: 99%
“…UnverrichtLundborg disease (EPM1), the most common form of progressive myoclonus epilepsy, is a rare autosomal disorder caused by loss-of-function mutations in the gene encoding cystatin B (CysB). [1][2][3] EPM1 has an onset of symptoms at 6 to 15 years of age, and progression with age leads to myoclonic and tonic-clonic seizures, 4,5 neurological decline, and severe ataxia. 4,6 CysB, a member of the cystatin family 1 of cysteine protease inhibitors, is mainly found in the cytosol and at lower levels in body fluids.…”
mentioning
confidence: 99%